Nilai profetik dan kelayakan kumpulan cerita rakyat Jawa Kalarahu sebagai bahan ajar apresiasi sastra di SMA - Dinar Anggraini; Mukh. Doyin (Universitas Ahmad Dahlan, 2026)
This study aims to describe the prophetic values contained in the collection of Javanese folktales in the book Kalarahu by Mardiyanto and to examine its relevance as literary appreciation teaching materials for senior high schools. The study employed a descriptive qualitative approach using content analysis methods. The data source consisted of the collection of Javanese folktales in Kalarahu, while the data were in the form of excerpts containing prophetic values. Data were collected through heuristic reading and note-taking techniques. The data were analyzed using hermeneutic reading based on Kuntowijoyo’s prophetic literary perspective. Data validity was ensured through theoretical triangulation and persistent observation. The findings reveal that the collection of Javanese folktales in Kalarahu contains three prophetic values: humanization, liberation, and transcendence. Humanization is reflected in encouraging goodness, maintaining brotherhood, and respecting others. Liberation is manifested through efforts to free people from ignorance, injustice, poverty, and various forms of social oppression. Transcendence is represented through praying, gratitude, trust in God, patience, sincerity, repentance, and hope in God. The collection of Javanese folktales in Kalarahu is considered relevant as literary appreciation teaching materials for senior high schools because it contains prophetic values that align with students’ characteristics and the objectives of literature learning in the Merdeka Curriculum.